Credit constraints and spillovers from foreign firms in China - Agarwal, Natasha; Milner, Chris; Riaño, Alejandro (Elsevier, 2014)
This paper examines whether credit constraints affect Chinese firms’ absorption of productivity spillovers originating from the activity of foreign-owned firms. Using firm-level data for 2001–2005, we find evidence of positive spillovers originating from foreign-owned firms from countries other than Hong Kong, Macau and Taiwan for non-state owned Chinese firms operating in the same industry and province. Using an index of external finance dependence to measure credit constraints, we find that only non-state-owned firms operating in industries with external finance dependence below the index median exhibit significantly positive spillovers from the activity of foreign firms.